COVID, physical education and prevention - Smith Palacio, Eulisis; Rodríguez, Bárbara; Matos-Duarte, Michelle (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2023)
This paper aims to promote the use of Dialogic Sessions in Physical Education to prevent the spread of COVID-19 in Primary Education and Compulsory Secondary Education by creating healthy habits related to the pandemic. Using Dialogic Sessions in Physical Education encourages discussion, debate, reasoning and decision-making to prevent the spread of the pandemic.